Continuing education at the libraries: the case of the José Figueres Ferrer Library of the Technological Institute of Costa Rica (ITCR) - Morales Roldán, Maritza (2011)
This article highlights the importance of Continuous Training as a process to improve production and professional development, not only of the organization but also of its staff in order to expand knowledge based and stay up-to-date on new technological advances. The authors summarized the experience in Continuous Training of the José Figueres Ferrer Library at the Instituto Tecnológico de Costa Rica; whose Continuous Training Program has contributed to enhance its staff`s professional competence